Moral Education Models in Traditional and Modern Pesantrens: A Comparative Ethnography of Character Building in Banten - Dadan Sunandar; Zakaria Syafei; Muhajir; Wasehudin (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
Islamic boarding schools shape students' character through intensive education, exemplary leadership (uswah hasanah), religious practices, and comprehensive moral development. This study analyzes the moral education models in two types of Pesantrens, encompassing guidance systems, implementation factors, and the internalisation of spiritual values. Employing a qualitative ethnographic approach, data were gathered through interviews, observations, and documentation. The analysis followed the stages of data condensation, display, and conclusion drawing, with validity ensured through triangulation. The findings reveal that: (1) The moral education model instills adab (etiquette), piety, and responsibility through worship, spiritual guidance, and social habituation grounded in the Quran and Hadith. (2) The educational process—comprising ritual worship, Quranic memorization, classical text (Kitab Kuning) studies, and methods such as exemplary behavior, counseling, and dialogue—plays a pivotal role in fostering discipline and deepening spiritual understanding. (3) The outcomes demonstrate significant positive behavioral shifts, including enhanced politeness, spiritual awareness, independence, and empathy. (4) Implementation is supported by routine worship and a conducive environment, though challenged by educator coordination gaps and external cultural influences via technology. (5) Comparative analysis indicates that while traditional (Salafiyah) Pesantrens focus heavily on adab and classical texts, modern Pesantrens integrate moral values systematically into the broader curriculum. Both models effectively cultivate religious character through discipline, respect, and social concern.